A Weak Bifurcation Theory for Discrete Time Stochastic Dynamical Systems - Cees Diks; Florian Wagener (Tinbergen Institute, 2006)
This article presents a bifurcation theory of smooth stochastic dynamical systems that are governed by everywhere positive transition densities. The local dependence structure of the unique strictly stationary evolution of such a system can be expressed by the ratio of joint and marginal probability densities; this 'dependence ratio' is a geometric invariant of the system. By introducing a weak equivalence notion of these dependence ratios, we arrive at a bifurcation theory for which in the compact case, the set of stable (non-bifurcating) systems is open and dense. The theory is illustrated with some simple examples.
Keywords: C14; C22; C32; 330; stochastic bifurcation theory